Urgensi Pembaharuan Hukum Mengenai Perlindungan Data Pribadi E-Commerce di Indonesia - Bram Freedrik Sangojoyo; Aurelius Kevin; David Brilian Sunlaydi (Universitas Muhammadiyah Purwokerto, 2022)
E-commerce in Indonesia is increasing, especially since the Covid-19 pandemic. Electronic transactions run effectively and efficiently because there are facilities in the e-commerce platform that provide a variety of products to help people meet their daily needs. The use of e-commerce platforms requires all users to register first using their name, phone number, e-mail, and some other personal data before they can take advantage of the facility. Unfortunately, there are cases of data leaks that are massively done by taking data contained in the e-commerce platform and sold freely on illegal websites. One of the factors that influence the occurrence of data leaks is the absence of comprehensive rules governing the protection of personal data in Indonesia. The purpose of this study is to analyze the form of the legal protection of personal data of e-commerce users in Indonesia and see the comparison of personal data protection laws in Indonesia with those in Malaysia and Singapore. The results explained that there are regulations in the form of ministerial regulations governing the protection of personal data electronically, but the rules do not provide data protection expressly and far behind the rules in some ASEAN countries such as Malaysia and Singapore, so there needs to be a renewal of the law regarding data protection in Indonesia by issuing regulations at the level of laws as regulated and implemented. n in the Personal Data Protection Act of Malaysia and Singapore which also conform to EU GDPR rules. It aims to tighten the security of data managed by private parties and impose strict sanctions on anyone who accesses, collects, and transports data in an unauthorized or unlawful manner.Keywords: Personal Data Protection, e-Commerce, Legal Renewal